Bio-inspired bi-stable piezoelectric harvester for broadband vibration energy harvesting. (15th October 2020) - Qian, Feng; Hajj, Muhammad R.; Zuo, Lei
Graphical abstract: Highlights: A bio-inspired bi-stable piezoelectric energy harvester is designed, prototyped, and tested. Dynamics and energy harvesting performance of the harvester are investigated. Harvester experiences local multiple high-frequency vibrations under low-frequency excitation. Average power output and frequency bandwidth increase significantly as the excitation level increases. Abstract: Inspired by the rapid shape transition of the Venus flytrap, a novel low-cost, bi-stable piezoelectric energy harvester is proposed, analyzed, and experimentally tested for the purpose of broadband energy harvesting. The harvester consists of a piezoelectric macro fiber composite (MFC) transducer, a tip mass, and two sub-beams with bending and twisting deformations created by pre-displacement constraints at the free ends using rigid tip-mass blocks. Different from bi-stable harvesters realized by nonlinear magnetic forces or residual stresses in laminate composites, the bio-inspired bi-stable piezoelectric energy harvester stores the potential energy induced by the mutual self-constraint of the sub-beams and harvests the large energy released during the rapid shape transition. Detailed design steps and principles are introduced and a prototype is fabricated to demonstrate and validate the concept. The experimentally measured nonlinear force–displacement curve of the harvester exhibits a discontinuous feature as the harvester jumps between the stable states. The dynamics of the proposed bio-inspired bi-stable piezoelectric energy harvester is investigated under sweeping frequency and harmonic excitations. The results show that the sub-beams of the harvester experience local vibrations including broadband high-frequency oscillations during the snap-through. The energy harvesting performance of the harvester is evaluated at different excitation levels over the frequency range of 9.0–14.0 Hz. Broadband energy harvesting is attained at relatively high excitation levels. An average power output of 0.193 mW for a load resistance of 8.2 k Ω is harvested at the excitation frequency of 10 Hz and amplitude of 4.0 g.